MULTIPLIKASI TUNAS PADA DUA VARIETAS PISANG (Musa acuminata L.) DENGAN PEMBERIAN BEBERAPA KONSENTRASI SITOKININ - Ayna, Qorry; Isminingsih, Sulastri; Susiyanti, Susiyanti; Yenny, Ratna Fitry (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2023)
This study aimed to investigate how the application of various cytokinin concentrations affects the shoot multiplication in two varieties of banana (Musa acuminata L.). The research was conducted at the Plant Physiology and Biotechnology Laboratory, Faculty of Agriculture, Sultan Ageng Tirtayasa University. The study was designed as a randomized complete block design, consisting of two factors. The first factor included two types of banana varieties: bagja (v1) and cavendish (v2). The second factor included six types of application of various concentrations of cytokinin, which were 1 mg/l BAP (k1), 2 mg/l BAP (k2), 3 mg/l BAP (k3), 1 mg/l kinetin (k4), 2 mg/l kinetin (k5), and 3 mg/l kinetin (k6). The results showed a significant difference in the effect of cavendish banana varieties explant on the height of the plant, with an average value of 3.26 cm. The application of various concentrations of cytokinin didn’t significantly affect the parameters of the height of the plant, shoot emergence time, number of shoots, and time of root emergence.Keywords: Bagja, Cavendish, Cytokinin, In Vitro Culture